2017
DOI: 10.25251/skin.1.2.7
|View full text |Cite
|
Sign up to set email alerts
|

Sarcoidosis Developing During Secukinumab Therapy: Case Report

Abstract: Introduction: Sarcoidosis is a systemic granulomatous inflammatory disease with an unknown etiology and complex pathogenesis. Existing literature supports the relationship of new-onset sarcoidosis with the use of a several biologic agents. Since the skin is the second most commonly involved organ in sarcoidosis and often precedes systemic involvement, dermatologists must be able to recognize its non-specific clinical presentation.Case Report: We present a 45 year old female with psoriatic arthritis who develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…Previous reports suggest a favorable effect of secukinumab in two cases of sarcoidosis associated with TNF antagonists (55,56). Conversely, our review of the literature identified two cases of sarcoidosis that either developed or worsened in patients taking secukinumab and ixekizumab (57,58). However, a previous multicentre, randomized, double blind, phase II trial, assessing the efficacy and safety of secukinumab in non-infectious uveitis did not identify any safety concerns in the included patients with sarcoidosis (n = 4) (59).…”
Section: Interleukin-17 Blockingmentioning
confidence: 64%
“…Previous reports suggest a favorable effect of secukinumab in two cases of sarcoidosis associated with TNF antagonists (55,56). Conversely, our review of the literature identified two cases of sarcoidosis that either developed or worsened in patients taking secukinumab and ixekizumab (57,58). However, a previous multicentre, randomized, double blind, phase II trial, assessing the efficacy and safety of secukinumab in non-infectious uveitis did not identify any safety concerns in the included patients with sarcoidosis (n = 4) (59).…”
Section: Interleukin-17 Blockingmentioning
confidence: 64%
“…When considering future treatment options for PsA, there remains concerns about risk of DISR with other targeted therapies. Secukinumab an IL-17 target that is NICE approved for PsA has been reported in one published case to have caused secukinumab-associated sarcoidosis [ 4 , 7 ]. Tofacitinib is a Janus kinase (JAK) inhibitor that has recently been approved by NICE for the treatment of PsA, and to date there have been no reports of JAK inhibitor-associated sarcoidosis.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6] To date, there are few reports of sarcoidosis observed with IL-17 inhibitors, four of them occurring with secukinumab. [1][2][3][4][5] Time to onset varied from 3.25 to 19.6 months. 1 There have also been reports of granuloma annulare associated with IL-17 inhibitors.…”
Section: Conflict Of Interestsmentioning
confidence: 99%
“…[1][2][3][4] Dermatological adverse events have been reported in phase II studies including alopecia, palmar-plantar erythrodysesthesia syndrome, stomatitis and nail changes. [1][2][3][4] Nail adverse events, which typically develop within 1-2 months of treatment initiation are typically of mildto-moderate severity. 4 The most reported events have been as follows: onychomadesis, nail discolouration, onycholysis, nails dystrophy, paronychia and onychoclasis.…”
mentioning
confidence: 99%